Evaluación de las condiciones térmico metabólicas en el área de producción de la empresa oriental industria alimenticia Oia. Cia. Ltda. Planta Estambul Quevedo y su incidencia en los trastornos sistémicos por calor. - Tuárez García, Diego Armando (2017)
The present research aims to determine the thermal-atmospheric conditions in which workers develop their activities and their incidence in systemic heat disorders such as syncope, edema, cramps, exhaustion and heat stroke, in addition to local disorders such as skin conditions, in The food processing plant Oriental Food Industry OIA Cía. Ltda., Located in the city of Quevedo at an altitude of 75 m s. N. M. Its objective is to reduce the incidence of occupational accidents and diseases by implementing preventive measures systems by carrying out engineering and administrative controls. As the initial stage of the investigation, the identification of the critical areas was carried out. The WBGT index was measured using the instruments and methods endorsed by ISO 7226, after which the results were evaluated to propose measures that reduce, control Or minimize the heat stress levels allowed under current regulations, these measures will guarantee the integrity and well-being of all workers involved in these processes.